Barnkalas på McDonald’s: Event marketing med förhinder - Brembeck, Helene (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
In this article birthday party rituals at McDonald’s are studied as hybrids of orderings of different actors: the company eager to create loyal customers, or at least to offer an event worth paying for, the parents wanting some relief, the children wanting to play and have fun, the staff eager to perform their professionalism, and the marketing agency wanting to promote their event concept. What looks like a smoothly running event following a consistent party manual, appears to consist of several competing orderings, or programs and anti-programs (Latour, 2000), offering different peak moments, sacrifices and gains for the actors involved.